Lead-cadmium fluorogermanate glasses and transparent glassceramics. Spectroscopy and structure - Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Bueno, L. A.; Dexpert-Ghys, J.; Gouveia-Neto, A. S.; Tambelli, C. C.; Donoso, J. P.; Magon, C. (Trans Tech Publications, 2006)
In Lead-cadmium fluorogermanate glasses (PbF2-CdF 2-PbGeO3) the addition of metal fluorides to the base PbGeO3 glass leads to a decrease of the glass transition temperature (Tg) and to an enhancement of the ionic conductivity properties. Based on different spectroscopic techniques (19F NMR, Ge K-edge X-ryas absorption and Raman scattering) an heterogeneous glass structure is proposed at the molecular scale, which can be described by fluoride rich regions permeating the metagermanate chains. The temperature dependence of the 19F NMR lineshapes and relaxation times exhibits the qualitative and quantitative features associated with the high fluoride mobility in these systems. Eu 3+ emission and vibronic spectra are used to follow the crystallization process leading to transparent glass ceramics.
Keywords: 19F NMR; Europium; Glass ceramics; Ionic conduction; Lanthanides; Oxyfluoride glasses; Vibronic spectrum; Cadmium; Glass transition; Relaxation processes